Home versus School Learning: A New Approach to Estimating the Effect of Class Size on Achievement - Mikael Lindahl (Institute for the Study of Labor (IZA), 2001)
I estimate the effect of class size on scholastic achievement using that schools are only in session during the school year and out of session during the summer. This seasonal feature of the schooling system makes it possible to control for unobservable pupil characteristics affecting both the level and change in achievement. Using Swedish data, I find that smaller classes generate higher achievement. A comparison with the results from applying the same data to the widely used value-added model is also made.
Keywords: I21; I28; H52; 330; Class size; summer learning; school-year learning; difference-in-differences; value-added model; Bildungsniveau; Allgemeinbildende Schule; Klassengröße; Schätzung; Schweden